An Autistic Student’s Journey in English Learning Strategies within ESP Contexts - Muhammad Nurul Muhlis; Putu Dian Danayanti Degeng (Universitas Islam Negeri Palopo, 2026)
Inclusive education in Indonesian vocational schools needs to pay more attention to the experiences of students with autism spectrum disorder (ASD), especially in English for Specific Purposes (ESP) lessons because require complex social communication. Unfortunately, the voices of autistic students are rarely explored because most research focuses on teachers' perspectives. This narrative inquiry study aims to determine how an autistic student experiences and understands English learning strategies in the context of ESP. This study adopts a neurodiversity framework, experiential theory, and inclusive pedagogy with data collection instruments using semi-structured interviews, systematic observations, and field reflections. Then analyzed using narrative thematic analysis. As a result, this study identified four related themes. First, structured routines that serve as the foundation for student’s emotional security and cognitive readiness. Second, the pace of instruction and clarity of instructions, which significantly influence his understanding and well-being. Third, modeling and visual-digital support, which serve as the primary pathways to authentic understanding. Fourth, vocational relevance serves as a source of sustained motivation and identity formation. This study also identified a pattern of masking—tendency to pretend to understand in order to maintain social conformity—which acts as an invisible barrier to authentic learning. Thus, this study contributes to the growing literature that places the autistic voice at the center of research in English as a Foreign Language Teaching and English for Specific Purposes. This study also offers evidence-based recommendations for designing inclusive ESP in vocational education in Indonesia.